(untitled) (Politeja, 2021)
In this paper the author tries to answer the question of what factors caused the great German author Thomas Mann to accept the official goals of World War I by focusing on his Reflections of a Nonpolitical Man. It also discusses Thomas Mann’s disagreements with his brother Heinrich Mann and his polemics with the ideas specific to the mainstream liberal thinking. Additionally, the article considers the context of the Polish reception of Thomas Mann. The author also discusses the problem of the topicality of the writer‘s attitude.